Factors affecting cyberbullying behaviours among university students: A review - Nur Shamsiah, Abdul Rahman; Noor Azida, Sahabudin; Eh Phon, Danakorn Nincarean; Mohd Faizal, Ab Razak; Anis Farihan, Mat Raffei (IEEE, 2023)
Cyberbullying, the act of intentionally causing harm to others through electronic communication, has emerged as a critical societal concern, particularly among university students. With the rapid proliferation of digital technologies, university campuses have become hotspots for cyberbullying incidents, necessitating a comprehensive understanding of the underlying factors driving this phenomenon. This paper presents a systematic review that aims to identify and analyze the key factors influencing cyberbullying behaviours among university students. The conceptual framework that was utilized to pinpoint the factors influencing university students' cyberbullying behaviours was examined in this study. According to a systematic screening of recent research articles (from 2013 to 2023) pertaining to online bullying behaviours among university students, the findings were given. After evaluating theoretical models and associated concepts, we suggest using the Theory of Planned Behaviour to evaluate factors influencing cyberbullying behaviours among university students. The findings of this study are discussed, and it is concluded that subjective norms, attitude, perceived behavioural control, social media use, and intentions all have the ability to influence university students' cyberbullying behaviours.